Slope Monitoring Study using Soil Mechanics Properties and 4-D Electrical Resistivity Tomography Methods - Bery, Andy Anderson (Springer Verlag, 2016)
In past applications of electrical resistivity survey, users commonly focussed on the Earth's subsurface to locate water table, bedrock, etc. Nowadays, this electrical resistivity method is used by engineers for shallow subsurface investigations. This paper presents the integration of soil mechanics properties with electrical resistivity tomography methods and recommends the proper selection of resistivity array (survey planning) and appropriate inversion constraint parameters (data processing) that are able to deliver optimum resistivity tomography model results. This study identifies the empirical correlations of the soil's properties such as shear strength parameters, moisture content, void ratio, porosity, saturation degree, and Atterberg's limits with the electrical resistivity values (resistivity tomography models). A total of 11 undisturbed clayey sand soil samples was collected at different distances, depths, and times and were tested under both infield and laboratory conditions during the slope monitoring period. The soil mechanics properties of the soil samples were obtained right after the electrical resistivity survey was made. It is shown that the electrical resistivity values are greatly influenced by the soil mechanics properties. Thus, the electrical resistivity (4-D) survey using the optimized Wenner- Schlumberger array (high data density) is capable of reliably enhancing the conventional outcome of the Earth's subsurface investigation